PELATIHAN IMPLEMENTASI KURIKULUM MERDEKA DI MADRASAH ALIYAH AL MUSTOFAWIYAH KARANGTENGAH CIANJUR - Adah Aliyah (Institut Madani Nusantara, 2023)
The lack of teachers' understanding of the concept of independent learning and difficulties in using e-learning technology are issues in the field. The aim of the community service activity is to equip teachers with an understanding of the concept of independent curriculum. The methods used include discussions, lectures, QA sessions, and mentoring using PowerPoint materials. This activity was carried out at Madrasah Aliyah Al Mustofawiyah Karangtengah, and the results have had a positive impact on teachers' understanding of creating high-quality teaching modules for independent learning curriculum.